Industrial Relations In Human Resource Management Study: Human Resource Development Strategy At The Police Education And Training Center - Malaahayati (Perkumpulan Dosen Muda (PDM) Bengkulu, 2026)
Purpose: This study aims to analyze the role of Industrial Relations within Human Resource Management as a strategic approach to human capital development at the Indonesian National Police Training and Education Institute (Lemdiklat Polri). The research emphasizes collaborative working relationships to enhance police personnel competencies. Methodology: A qualitative approach was applied using literature review and institutional policy analysis, supported by thematic interpretation of industrial relations principles, human resource development, and police education functions. Results: The study indicates that effective more effective human resource development strategies through the implementation of data-based planning, accelerated digitalization, competency-based curriculum updates, and integration of modern technology. Findings: The findings indicate that human resource development at the National Police Education and Training Institute (Lemdiklat Polri) is still hampered by non-data-driven planning, suboptimal system digitalization, training methods that do not focus on competency and performance, and minimal use of AI and automation technology. Novelty: This research introduces an integrative framework linking industrial relations to competency-based development in a police organization. Originality: It offers a unique perspective by positioning human relations synergy as a core driver of HR development in police training institutions. Conclusion: Industrial Relations serve as a strategic foundation for enhancing Lemdiklat’s performance through measurable quality improvement. Type of Paper: This paper is an empirical research paper.